Arranjos produtivos locais na perspectiva da teoria do capital social: um estudo no APL moveleiro de Marco/CE - Gobb, Raquel Lorena (2008)
This study aims to characterize the social capital constituted in a Local Productive Arrangement - LPA of furniture located in the northern state of Ceará, focusing their operational aspects, procedural and organizational. The importance of the study stems from the use of the theory of social capital, a body emerging theory that is based on the mobilization of human factors in nature collective, as an alternative to traditional explanatory contributions of economic and social development. The research is of a qualitative nature of the types exploratory and descriptive. For this, a theoretical research in depth was undertaken, and a search field in the case study, with the unit of analysis the productive cluster of furniture in Marco/CE. The data collection through interviews semi-directives and semi-structured was conducted with 25 individual and institutional actors, representing the value chain of the productive cluster. The documentary analysis and content allowed describe economic, social and institutional results, in terms of generating income, employment and the development of individual and organizational skills, referenced in elements of analysis which are the dimensions cognitive, relational and structural theory of the social capital, constituting valid benchmarks for the strategic management of organizations and individuals.